The Relationship of Self-Compassion with Forgiveness in Teenage Victims of Divorce in Indramayu - Maulidia Fatimah Latifannisa; Mirna Wahyu Agustina (IJIP : Indonesian Journal of Islamic Psychology, 2024)
Forgiveness is turning negative things into positive ones for someone who has caused pain to themselves. Forgiveness can be applied to improve the quality of life and maintain psychological well-being by avoiding harboring excessive anger and disappointment. Based on previous research, it is stated that forgiveness can make individuals feel well-being in their lives, away from feelings of revenge and disappointment. In contrast, one of the factors that can influence forgiveness is self-compassion. This research was conducted to scientifically examine the relationship between self-compassion and forgiveness in teenage victims of divorce in Indramayu. The sample used was 350 teenagers with divorced parents and was taken using a purposive sampling technique. The instruments for collecting data in this research used self-compassion and forgiveness scales. Data analysis uses Pearson product moment correlation analysis. The results of data analysis show a correlation coefficient of 0.511 with a value of p = 0.000 (p<0.05), which shows a significant relationship between self-compassion and forgiveness in teenage divorce victims in Indramayu and has a positive relationship direction.